Association of myelin peptide with vitamin D prevents autoimmune encephalomyelitis development - Mimura, L. A.N. [UNESP]; Chiuso-Minicucci, F. [UNESP]; Fraga-Silva, T. F.C. [UNESP]; Zorzella-Pezavento, S. F.G. [UNESP]; França, T. G.D. [UNESP]; Ishikawa, L. L.W. [UNESP]; Penitenti, M.; Ikoma, M. R.V.; Sartori, A. [UNESP] (Elsevier, 2016)
Multiple sclerosis is a chronic, inflammatory and demyelinating disease of the central nervous system (CNS). As there is no cure for this disease, new therapeutic strategies and prophylactic measures are necessary. We recently described the therapeutic activity of the association between myelin oligodendrocyte glycoprotein peptide (MOG) and active vitamin D3 (VitD) against experimental autoimmune encephalomyelitis (EAE). The objective of this work was to evaluate the prophylactic potential of this association in EAE. C57BL/6 mice were vaccinated with MOG in the presence of VitD and then subjected to EAE induction. Animals were euthanized 7 and 19 days after disease induction and the following parameters were evaluated: body weight, clinical score, inflammatory process in the CNS, amount of dendritic cells (DCs) and regulatory T cells in the spleen and cytokine production by spleen and CNS cell cultures. Vaccination with MOG associated with VitD determined a drastic reduction in clinical score, body weight loss, CNS inflammation, DCs maturation and also in the production of cytokines by CNS and spleen cell cultures. Collectively, our data indicate that this association prevents EAE development. A similar effect from specific self-antigens associated with VitD is expected in other autoimmune conditions and deserves to be experimentally appraised.
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Myelin oligodendrocyte glycoprotein; Tolerogenic adjuvant; Vitamin D3